Hexagonal metal nanosheet and preparation method thereof

By forming a periodic photoresist pattern hole array on the substrate and performing magnetron sputtering to deposit the metal film layer, the problems of different sizes of hexagonal gold nanosheets, poor dispersion, and difficult to remove organic matter residues in the prior art are solved, and large-scale production of hexagonal metal nanosheets is achieved in a uniform size and good dispersion.

CN119703049APending Publication Date: 2025-03-28杭州邦齐州科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411897254.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

It is difficult to produce hexagonal gold nanosheets in large quantities in the prior art, and the products have different sizes, poor dispersion, and it is difficult to remove organic residues.

Method used

A hexagonal metal nanosheet template was prepared by semiconductor production process, and periodic photoresist pattern hole array was formed by coating the substrate, exposure and development, and then magnetron sputtering was performed to deposit the metal film layer and remove the glue, and finally the metal film layer formed a hexagonal structure by annealing.

Benefits of technology

The hexagonal metal nanosheets are uniform in size, good dispersion, and do not contain organic matter. They can be produced on a large scale with few defects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119703049A_ABST
    Figure CN119703049A_ABST
Patent Text Reader

Abstract

The invention provides a hexagonal metal nanosheet and a preparation method thereof, and belongs to the technical field of metal nanosheet preparation. According to the method for preparing the hexagonal metal nanosheet template by adopting a semiconductor production process, a regularly arranged metal nanosheet structure is obtained. No organic matter is used, so that the interference of the organic matter on a finished product is reduced; in addition, a structure with good periodic arrangement on a 6-inch, 8-inch or 12-inch substrate can be obtained at a time, defects are few, and the generation of the defects is greatly reduced. The hexagonal metal nanosheet provided by the invention is uniform in size, good in dispersity and free of organic matters.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal nanosheet preparation, and particularly relates to a hexagonal metal nanosheet and a preparation method thereof. Background Art

[0002] Anisotropic noble metal nanostructures are currently very attractive materials due to their unique physical and chemical properties. Among them, gold nanosheets play an important role in surface enhanced Raman scattering, biomedicine, plasma sensors and catalysts due to their good photoelectric properties, high specific surface area and selective adsorption on specific crystal planes.

[0003] There are many methods for preparing hexagonal gold nanosheets, but most of these methods have some problems and cannot be mass-produced. For example, the liquid phase reduction method can simply and quickly obtain gold nanosheets with good morphology, but the synthesized gold nanosheets are of different sizes and the residual capping agent is difficult to remove; the hydrothermal method can mass-produce uniform and regular gold nanosheets with high purity and yield and low cost, but organic matter is also difficult to remove and the product has poor dispersibility. Summary of the invention

[0004] In view of this, the object of the present invention is to provide a hexagonal metal nanosheet and a preparation method thereof. The hexagonal metal nanosheet provided by the present invention has uniform size and good dispersibility and does not contain organic matter.

[0005] In order to achieve the above object, the present invention provides the following scheme:

[0006] The present invention provides a method for preparing hexagonal metal nanosheets, which is characterized by comprising the following steps:

[0007] Coating a photoresist on a substrate to form a photoresist coating; sequentially exposing and developing the photoresist coating to form a periodic photoresist pattern hole array in the photoresist coating, thereby obtaining a substrate having periodic photoresist pattern holes; the periodic photoresist pattern hole array is formed by arranging a plurality of photoresist pattern holes that are not in contact with each other; the photoresist pattern holes are cylindrical hole structures;

[0008] The substrate having periodic photoresist pattern holes is subjected to magnetron sputtering to deposit a metal film layer to obtain a coated photoresist substrate;

[0009] Debonding the coated photoresist substrate to obtain a cylindrical metal film layer substrate;

[0010] The cylindrical metal film layer substrate is annealed to form the cylindrical metal film layer into a hexagon, thereby obtaining the hexagonal metal nanosheet.

[0011] Preferably, the diameter of the photoresist pattern hole is 330-370 nm, and the height is 690-710 nm; the distance between adjacent photoresist pattern holes is 594-606 nm.

[0012] Preferably, the metal in the metal film layer includes gold or silver.

[0013] Preferably, the thickness of the metal film layer is 38.5-41.5 nm, and the surface roughness is ≤5 nm.

[0014] Preferably, the coating comprises spin coating; the spin coating comprises: dropping the photoresist onto the substrate, and then increasing the rotation speed to 3200-3600 rpm within 4-6 seconds; the total time for coating the photoresist is 25-30 seconds.

[0015] Preferably, the exposure time is 30 to 40 seconds, and the development time is 80 to 90 seconds.

[0016] Preferably, the vacuum degree of the magnetron sputtering is 6.4×10 -6 ~6.6×10 -6 Pa, argon pressure is 1.2-1.3 Pa, sputtering power is 70-73 W, sample stage speed is 5-6 rpm, sputtering time is 600-800 s, sputtering rate is 0.050-0.055 nm·s -1 .

[0017] Preferably, the debonding includes wet debonding and dry oxygen debonding.

[0018] Preferably, the annealing temperature is 800-900° C. and the time is 30-40 min.

[0019] The present invention provides hexagonal metal nanosheets prepared by the preparation method described in the above scheme, wherein the average diameter of the hexagonal metal nanosheets is 105nm, the height is 42.9nm, each side length is 65nm, and the distance between adjacent hexagonal metal nanosheets is 606nm.

[0020] The invention provides a method for preparing a hexagonal metal nanosheet, comprising the following steps: coating a photoresist on a substrate to form a photoresist coating; sequentially exposing and developing the photoresist coating to form a periodic photoresist pattern hole array on the photoresist coating to obtain a substrate with periodic photoresist pattern holes; the periodic photoresist pattern hole array is formed by arranging a plurality of photoresist pattern holes that are not in contact with each other; the photoresist pattern holes are cylindrical hole structures; magnetron sputtering the substrate with the periodic photoresist pattern holes to deposit a metal film layer to obtain a coated photoresist substrate; stripping the coated photoresist substrate to obtain a cylindrical metal film layer substrate; annealing the cylindrical metal film layer substrate to form a hexagon in the cylindrical metal film layer to obtain the hexagonal metal nanosheet.

[0021] The present invention adopts a method for preparing a hexagonal metal nanosheet template using a semiconductor production process to obtain a regularly arranged metal nanosheet structure. The present invention does not require the use of organic matter, which reduces the interference of organic matter on the finished product; in addition, a periodically arranged good structure on a 4-inch, 6-inch, 8-inch or 12-inch substrate (all referring to the diameter of the substrate) can be obtained at one time, with few defects and greatly reduced defect generation. The hexagonal metal nanosheets provided by the present invention are uniform in size, have good dispersibility, and do not contain organic matter.

[0022] Furthermore, the present invention adjusts the size of the required structure by controlling the aperture of the photolithography pattern hole and the thickness of the metal film layer, thereby shortening the preparation time and improving the experimental efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0024] Figure 1 This is a simplified flow chart of the preparation of hexagonal metal nanosheets according to the present invention, wherein: 1-quartz glass substrate, 2-photoresist, 3-metal film layer, 4-nanostructure;

[0025] Figure 2 This is a SEM top view of the hexagonal gold nanosheet structure of Example 1 of the present invention;

[0026] Figure 3 This is an AFM top view of the elliptical gold nanosheet structure of Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0027] The present invention provides a method for preparing hexagonal metal nanosheets, comprising the following steps:

[0028] Coating a photoresist on a substrate to form a photoresist coating; sequentially exposing and developing the photoresist coating to form a periodic photoresist pattern hole array in the photoresist coating, thereby obtaining a substrate having periodic photoresist pattern holes; the periodic photoresist pattern hole array is formed by arranging a plurality of photoresist pattern holes that are not in contact with each other; the photoresist pattern holes are cylindrical hole structures;

[0029] The substrate having periodic photoresist pattern holes is subjected to magnetron sputtering to deposit a metal film layer to obtain a coated photoresist substrate;

[0030] Debonding the coated photoresist substrate to obtain a cylindrical metal film layer substrate;

[0031] The cylindrical metal film layer substrate is annealed to form the cylindrical metal film layer into a hexagon, thereby obtaining the hexagonal metal nanosheet.

[0032] Unless otherwise specified, the materials and equipment used in the present invention are commercially available products.

[0033] Figure 1 The simplified flow chart of the preparation of hexagonal metal nanosheets of the present invention, wherein: 1-quartz glass substrate, 2-photoresist, 3-metal film layer, 4-nanostructure. Figure 1 As shown, the present invention coats photoresist on a substrate to form a photoresist coating.

[0034] In the present invention, the substrate preferably includes a silicon wafer substrate or a quartz glass wafer substrate.

[0035] Before coating the photoresist, the present invention preferably cleans and dries the substrate; the cleaning preferably includes acid cleaning, water cleaning and alkaline cleaning performed in sequence. In the present invention, the reagents for the acid cleaning preferably include concentrated sulfuric acid and hydrogen peroxide; the mass concentration of the concentrated sulfuric acid is preferably 98%; the mass concentration of the hydrogen peroxide is preferably 30%; the volume ratio of the concentrated sulfuric acid and hydrogen peroxide is preferably 7:3; the time for the acid cleaning is preferably 20 minutes. In the present invention, the water cleaning preferably involves immersing the acid-cleaned substrate in water for ultrasonic treatment; the water cleaning time is preferably 20 minutes. The present invention can wash away the acid solution remaining on the surface of the substrate by water cleaning. In the present invention, the power of the ultrasound is preferably 50 to 80W.

[0036] After the water washing is completed, the present invention preferably blows the washed substrate dry with nitrogen and then performs alkali washing. In the present invention, the reagents for the alkali washing preferably include ammonia water, hydrogen peroxide and water; the concentration of the ammonia water is preferably 0.9g / mL; the mass concentration of the hydrogen peroxide is preferably 30%; the volume ratio of the ammonia water, hydrogen peroxide and water is preferably 1:5:100; the time of the alkali washing is preferably 5 minutes. The present invention can neutralize the acid solution remaining on the surface of the substrate through alkali washing. In the present invention, the drying temperature is preferably 60°C.

[0037] In the present invention, the coating preferably includes spin coating; the spin coating preferably includes: dropping the photoresist on the substrate, and then within 4 to 6 seconds, which can be 4 seconds, 5 seconds or 6 seconds in the embodiment of the present invention, the rotation speed is increased to 3200 to 3600 rpm, which can be 3200 rpm, 3300 rpm, 3400 rpm, 3450 rpm, 3500 rpm or 3600 rpm in the embodiment of the present invention. In the present invention, the total time of coating the photoresist is preferably 25 to 30 seconds, which can be 25 seconds, 26 seconds, 27 seconds, 28 seconds, 29 seconds or 30 seconds in the embodiment of the present invention. In the present invention, the model of the photoresist preferably includes ULTRA-i123.

[0038] After the coating of the photoresist is completed, the present invention sequentially exposes and develops the photoresist coating so that the photoresist coating forms a periodic photoresist pattern hole array, thereby obtaining a substrate with periodic photoresist pattern holes; the periodic photoresist pattern hole array is formed by arranging a plurality of photoresist pattern holes that are not in contact with each other; the photoresist pattern holes are cylindrical hole structures.

[0039] In the present invention, the exposure time is preferably 30 to 40 seconds, and in the embodiments of the present invention, it can be 30 seconds, 32 seconds, 34 seconds, 35 seconds, 36 seconds, 38 seconds or 40 seconds. The present invention transfers the pattern on the photolithography mask plate to the photoresist coating through exposure.

[0040] After completing the exposure, the present invention preferably uses a hot plate to post-bake the exposed substrate; the post-bake temperature is preferably 110-200°C, and in the embodiments of the present invention, it can be 110°C, 120°C, 140°C, 150°C, 160°C, 180°C or 200°C; the post-bake time is preferably 1-2 minutes, and in the embodiments of the present invention, it can be 1 minute or 2 minutes.

[0041] In the present invention, the development time is preferably 80 to 90 seconds, and in the embodiments of the present invention, it can be 80 seconds, 82 seconds, 84 seconds, 85 seconds, 86 seconds, 88 seconds or 90 seconds. The present invention forms a periodic photoresist pattern hole array on the exposed photoresist coating through development.

[0042] The present invention exposes the substrate with periodic photoresist pattern holes through exposure and development, so that the bottom surface in each photoresist pattern hole is exposed to the substrate, and the photoresist coating is retained outside the photoresist pattern hole.

[0043] After the development is completed, the present invention preferably washes the developed substrate with water; the washing time is preferably 1.3 to 1.5 minutes.

[0044] In the present invention, the diameter of the photoresist pattern hole is preferably 330-370nm, and in the embodiment of the present invention, it can be 330nm, 340nm, 350nm, 360nm, 365nm or 370nm; the height of the photoresist pattern hole is preferably 690-710nm, and in the embodiment of the present invention, it can be 690nm, 692nm, 694nm, 700nm, 705nm or 710nm. In the present invention, the distance between adjacent photoresist pattern holes is preferably 594-606nm, and in the embodiment of the present invention, it can be 594nm, 600nm, 602nm, 604nm, 605nm or 606nm.

[0045] After obtaining the substrate with periodic photoresist pattern holes, the present invention performs magnetron sputtering on the substrate with periodic photoresist pattern holes to deposit a metal film layer to obtain a coated photoresist substrate.

[0046] In the present invention, the metal in the metal film layer preferably includes gold or silver. In the present invention, the thickness of the metal film layer is preferably 38.5 to 41.5 nm, and in the embodiment of the present invention, it can be 38.5 nm, 39 nm, 40 nm, 40.5 nm, 41 nm or 41.5 nm; the surface roughness (Ra) of the metal film layer is preferably ≤5 nm.

[0047] In the present invention, the vacuum degree of the magnetron sputtering is preferably 6.4×10 -6 ~6.6×10 -6 Pa, in the embodiment of the present invention, can be 6.4×10 -6 Pa, 6.5×10 -6 Pa or 6.6×10 -6Pa; the argon pressure of the magnetron sputtering is preferably 1.2-1.3 Pa, and in the embodiment of the present invention, it can be specifically 1.2 Pa or 1.3 Pa; the sputtering power of the magnetron sputtering is preferably 70-73 W, and in the embodiment of the present invention, it can be specifically 70 W, 71 W, 72 W or 73 W; the sample stage rotation speed of the magnetron sputtering is preferably 5-6 rpm, and in the embodiment of the present invention, it can be specifically 5 rpm or 6 rpm; the sputtering time of the magnetron sputtering is preferably 600-800 s, and in the embodiment of the present invention, it can be specifically 600 s, 650 s, 680 s, 700 s, 750 s, 780 s or 800 s; the sputtering rate of the magnetron sputtering is preferably 0.050-0.055 nm·s -1 , in the embodiment of the present invention, it can be 0.05nm·s -1 , 0.052nm·s -1 , 0.054nm·s -1 or 0.055nm·s -1 .

[0048] The invention deposits the metal film layer on the photoresist coating outside the photoresist pattern hole and on the substrate inside the photoresist pattern hole through magnetron sputtering.

[0049] After obtaining the coated photoresist substrate, the present invention removes the coated photoresist substrate to obtain a cylindrical metal film layer substrate.

[0050] In the present invention, the photoresist coating outside the photoresist pattern hole and the metal film layer plated on the photoresist coating are removed by debonding, and the metal film layer on the substrate inside the photoresist pattern hole is retained.

[0051] In the present invention, the degumming preferably includes wet degumming and dry oxygen degumming. In the present invention, the wet degumming preferably includes: immersing the coated photoresist substrate in a degumming solution; the degumming solution preferably includes YPS-1500.

[0052] After the wet stripping is completed, the present invention preferably cleans the wet stripping substrate to remove impurities.

[0053] In the present invention, the oxygen flow rate of the dry oxygen stripping is preferably 290-300sccm, and in an embodiment of the present invention, it can be specifically 290sccm, 295sccm, 298sccm or 300sccm; the power of the dry oxygen stripping is preferably 500-550W, and in an embodiment of the present invention, it can be specifically 500W, 510W, 520W, 530W, 540W or 550W; the chamber pressure of the dry oxygen stripping is preferably 60-62Pa, and in an embodiment of the present invention, it can be specifically 60Pa, 61Pa or 62Pa; the time of the dry oxygen stripping is preferably 7-15min, and in an embodiment of the present invention, it can be specifically 7min, 10min, 12min or 15min.

[0054] After the degumming is completed, the present invention preferably cleans the degummed substrate; the cleaning is preferably performed by rinsing with water for 1 to 2 minutes.

[0055] After obtaining the cylindrical metal film layer substrate, the present invention anneals the cylindrical metal film layer substrate to form the cylindrical metal film layer into a hexagon, thereby obtaining the hexagonal metal nanosheet.

[0056] In the present invention, the annealing temperature is preferably 800-900°C, and in embodiments of the present invention, it can be 800°C, 820°C, 840°C, 860°C, 880°C, 890°C or 900°C; the annealing time is preferably 30-40min, and in embodiments of the present invention, it can be 30min, 32min, 34min, 36min, 38min or 40min.

[0057] After the annealing is completed, the present invention preferably cleans the annealed substrate; the cleaning preferably includes cleaning with ethanol and water in sequence.

[0058] The present invention provides hexagonal metal nanosheets prepared by the preparation method described in the above scheme, wherein the average diameter of the hexagonal metal nanosheets is 105nm, the height is 42.9nm, each side length is 65nm, and the distance between adjacent hexagonal metal nanosheets is 606nm.

[0059] In order to further illustrate the present invention, a hexagonal metal nanosheet and a preparation method thereof provided by the present invention are described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0060] Example 1

[0061] A quartz glass substrate with a diameter of 4 inches was placed in a mixture of concentrated sulfuric acid (98wt%) and hydrogen peroxide (30wt%) in a volume ratio of 7:3 for pickling for 20 minutes, then soaked in pure water and ultrasonicated for 20 minutes, and then dried with nitrogen. A mixture of ammonia water (0.9g / mL), hydrogen peroxide (30wt%) and pure water in a volume ratio of 1:5:100 was used to neutralize the residual concentrated sulfuric acid for 5 minutes, and then dried at 60°C for standby use for photolithography.

[0062] Specifically, a photoresist (model ULTRA-i123) is spin-coated on a quartz glass substrate to form a photoresist coating: the photoresist (automatically dispensed by a machine, the amount of photoresist is 3-4 mL) is dripped onto the quartz glass substrate, and then the rotation speed is increased to 3600 rpm within 6 seconds, and the total spin coating time is 25 seconds;

[0063] The photoresist coating is sequentially subjected to exposure for 35 seconds, post-baking at 150° C. for 1 minute, development for 85 seconds and water washing for 1.5 minutes, so that the photoresist coating forms a periodic photoresist pattern hole array, and a substrate with periodic photoresist pattern holes is obtained. The periodic photoresist pattern hole array is formed by arranging a plurality of photoresist pattern holes that do not contact each other, the bottom surface of each photoresist pattern hole exposes the substrate, and the photoresist coating is retained outside the photoresist pattern hole. The photoresist pattern hole is a cylindrical hole structure, the diameter of the photoresist pattern hole is 360nm, the height is 705nm, and the distance between adjacent photoresist pattern holes is 606nm.

[0064] The substrate with periodic photoresist pattern holes is coated with a nano-gold film layer by magnetron sputtering, and the nano-gold film layer is deposited on the photoresist coating outside the photoresist pattern holes and on the substrate inside the photoresist pattern holes to obtain a gold-coated photoresist substrate. The thickness of the nano-gold film layer is 40nm, and the surface roughness is Ra≤5nm. The magnetron sputtering conditions are: the target material is a gold target material, and the vacuum degree is 6.4×10 -6 Pa, argon pressure is 1.3 Pa, magnetron sputtering power is 70 W, sample stage speed is 6 rpm, sputtering time is 800 s, and sputtering rate is 0.050 nm·s -1 At this time, the gold-plated photoresist substrate is composed of a quartz glass substrate, a photoresist pattern and a nano-gold film layer from bottom to top.

[0065] The nano-gold film-coated photoresist substrate was immersed in an organic solvent-type degumming solution (the degumming solution, i.e., the photoresist stripping solution, was purchased from Yixin Microelectronic Materials (Nantong) Co., Ltd.) for 10 minutes for wet degumming. After the degumming was completed, the nano-gold film-coated photoresist substrate was cleaned with deionized water; and it was placed flat again in the sample chamber of the plasma degumming machine, and dry oxygen degumming was performed according to the set program conditions. The conditions were: the oxygen flow rate was 300sccm, the power was 550W, the pressure in the chamber was 60Pa, and the degumming time was 15min. The photoresist coating outside the photoresist pattern hole and the nano-gold film layer plated on the photoresist coating were removed, and the nano-gold film layer on the substrate inside the photoresist pattern hole was retained to obtain a cylindrical nano-gold film layer substrate.

[0066] The cylindrical nano-gold film substrate was rinsed with deionized water for 2 minutes and annealed in a box furnace at a temperature of 900° C. for 40 minutes. After the annealing was completed, the sample was taken out after cooling to room temperature and washed (first with ethanol and then with deionized water) to obtain a nanostructure template, i.e., a hexagonal gold nanosheet.

[0067] Figure 2 This is a SEM top view of the hexagonal gold nanosheet structure of Example 1 of the present invention, as shown Figure 2 As shown. The nanostructure arrangement has a certain periodicity and presents a hexagonal morphology with good dispersion. According to measurements, the average diameter of the hexagonal gold nanosheet structure is 105nm, the height is 42.9nm, the distance between adjacent hexagonal gold nanosheet particles is about 606nm, and the length of each side is about 65nm.

[0068] Comparative Example 1

[0069] The steps are the same as those in Example 1, except that the annealing temperature is 600° C. and the time is 60 min.

[0070] A quartz glass substrate with a diameter of 4 inches was placed in a mixture of concentrated sulfuric acid (98wt%) and hydrogen peroxide (30wt%) in a volume ratio of 7:3 for pickling for 20 minutes, then soaked in pure water and ultrasonicated for 20 minutes, and then dried with nitrogen. A mixture of ammonia water (0.9g / mL), hydrogen peroxide (30wt%) and pure water in a volume ratio of 1:5:100 was used to neutralize the residual concentrated sulfuric acid for 5 minutes, and then dried at 60°C for standby use for photolithography.

[0071] Specifically, a photoresist (model ULTRA-i123) is spin-coated on a quartz glass substrate to form a photoresist coating: the photoresist (automatically dispensed by a machine, the amount of photoresist is 3-4 mL) is dripped onto the quartz glass substrate, and then the rotation speed is increased to 3600 rpm within 6 seconds, and the total spin coating time is 25 seconds;

[0072] The photoresist coating is sequentially subjected to exposure for 35 seconds, post-baking at 150° C. for 1 minute, development for 85 seconds and water washing for 1.5 minutes, so that the photoresist coating forms a periodic photoresist pattern hole array, and a substrate with periodic photoresist pattern holes is obtained. The periodic photoresist pattern hole array is formed by arranging a plurality of photoresist pattern holes that do not contact each other, the bottom surface of each photoresist pattern hole exposes the substrate, and the photoresist coating is retained outside the photoresist pattern hole. The photoresist pattern hole is a cylindrical hole structure, the diameter of the photoresist pattern hole is 360nm, the height is 705nm, and the distance between adjacent photoresist pattern holes is 606nm.

[0073] The substrate with periodic photoresist pattern holes is coated with a nano-gold film layer by magnetron sputtering, and the nano-gold film layer is deposited on the photoresist coating outside the photoresist pattern holes and on the substrate inside the photoresist pattern holes to obtain a gold-coated photoresist substrate. The thickness of the nano-gold film layer is 40nm, and the surface roughness is Ra≤5nm. The magnetron sputtering conditions are: the target material is a gold target material, and the vacuum degree is 6.4×10 -6 Pa, argon pressure is 1.3 Pa, magnetron sputtering power is 70 W, sample stage speed is 6 rpm, sputtering time is 800 s, and sputtering rate is 0.050 nm·s -1 At this time, the gold-plated photoresist substrate is composed of a quartz glass substrate, a photoresist pattern and a nano-gold film layer from bottom to top.

[0074] The nano-gold film-coated photoresist substrate was immersed in an organic solvent-type degumming solution (the degumming solution, i.e., the photoresist stripping solution, was purchased from Yixin Microelectronic Materials (Nantong) Co., Ltd.) for 10 minutes for wet degumming. After the degumming was completed, the nano-gold film-coated photoresist substrate was cleaned with deionized water; and it was placed flat again in the sample chamber of the plasma degumming machine, and dry oxygen degumming was performed according to the set program conditions. The conditions were: the oxygen flow rate was 300sccm, the power was 550W, the pressure in the chamber was 60Pa, and the degumming time was 15min. The photoresist coating outside the photoresist pattern hole and the nano-gold film layer plated on the photoresist coating were removed, and the nano-gold film layer on the substrate inside the photoresist pattern hole was retained to obtain a cylindrical nano-gold film layer substrate.

[0075] The cylindrical nano-gold film substrate was rinsed with deionized water for 2 minutes and annealed in a box furnace at a temperature of 600°C for 60 minutes. After the annealing was completed, the sample was taken out after cooling to room temperature and washed (first with ethanol and then with deionized water) to obtain the following Figure 3 The nanostructure template shown is an elliptical gold nanosheet (which can be understood as an intermediate in the transformation into a hexagonal structure).

[0076] According to measurement, the average diameter of the short side of the elliptical gold nanosheet structure is 161nm, the average diameter of the long side is 246nm, the height is 39nm, and the distance between adjacent elliptical gold nanosheet particles is about 605nm.

[0077] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing hexagonal metal nanosheets, characterized in that: The following steps are involved: coating a photoresist on the substrate to form a photoresist coating; Exposing and developing the photoresist coating in sequence, so that the photoresist coating forms a periodic photoresist pattern hole array, thereby obtaining a substrate having periodic photoresist pattern holes; The periodic photoresist pattern hole array is formed by arranging a plurality of photoresist pattern holes that are not in contact with each other; The photoresist pattern hole is a cylindrical hole structure; The substrate having periodic photoresist pattern holes is subjected to magnetron sputtering to deposit a metal film layer to obtain a coated photoresist substrate; Debonding the coated photoresist substrate to obtain a cylindrical metal film layer substrate; The cylindrical metal film layer substrate is annealed to form the cylindrical metal film layer into a hexagon, thereby obtaining the hexagonal metal nanosheet.

2. The preparation method according to claim 1, characterized in that: The diameter of the photoresist pattern hole is 330-370nm, and the height is 690-710nm; the distance between adjacent photoresist pattern holes is 594-606nm.

3. The preparation method according to claim 1, characterized in that: The metal in the metal film layer includes gold or silver.

4. The preparation method according to claim 1 or 3, characterized in that: The thickness of the metal film layer is 38.5-41.5 nm, and the surface roughness is ≤5 nm.

5. The preparation method according to claim 1 or 2, characterized in that: The coating includes spin coating; the spin coating includes: dropping the photoresist on the substrate, and then increasing the rotation speed to 3200-3600 rpm within 4-6 seconds; the total time for coating the photoresist is 25-30 seconds.

6. The preparation method according to claim 1, 2 or 3, characterized in that: The exposure time is 30 to 40 seconds, and the development time is 80 to 90 seconds.

7. The preparation method according to claim 1, characterized in that: The vacuum degree of the magnetron sputtering is 6.4×10 -6 ~6.6×10 -6 Pa, argon pressure is 1.2-1.3 Pa, sputtering power is 70-73 W, sample stage speed is 5-6 rpm, sputtering time is 600-800 s, sputtering rate is 0.050-0.055 nm·s -1 .

8. The preparation method according to claim 1 or 7, characterized in that: The debonding includes wet debonding and dry oxygen debonding.

9. The preparation method according to claim 1, 2, 3 or 7, characterized in that: The annealing temperature is 800-900° C. and the annealing time is 30-40 minutes.

10. The hexagonal metal nanosheet prepared by the preparation method according to any one of claims 1 to 9, characterized in that: The average diameter of the hexagonal metal nanosheets is 105 nm, the height is 42.9 nm, each side length is 65 nm, and the distance between adjacent hexagonal metal nanosheets is 606 nm.